Knowledge and prevention practices of hand, foot and mouth disease (HFMD) among parents who visited Hospital Pakar Universiti Sains Malaysia (HPUSM) - Sakri, Nur Fazlin Adrin (Universiti Sains Malaysia, 2025)
Hand, Foot and Mouth Disease (HFMD) is a highly contagious viral illness that primarily affects children. While typically mild, severe complications may arise without timely intervention. This cross-sectional study aimed to assess the level of knowledge and preventive practices regarding HFMD among parents who visited Hospital Pakar Universiti Sains Malaysia (HPUSM), and to examine the relationship between knowledge and preventive behaviour. A total of 191 parents participated using a validated, self-administered questionnaire adapted from previous studies. The instruments measured socio-demographic characteristics, knowledge of HFMD, and preventive practices. Responses were classified using Bloom’s cut-off points. Results showed that 52.8% of respondents had a high level of knowledge, 44.6% moderate, and 0.5% low. In terms of preventive practices, 87.2% reported good practices, 10.8% moderate, and none reported poor practices. Common measures included frequent handwashing, avoiding crowded areas during outbreaks, and cleaning toys and surfaces. However, some misconceptions persisted, particularly regarding modes of transmission and the severity of the disease. Pearson’s correlation analysis revealed a weak, positive but statistically insignificant relationship (r = 0.118, p = 0.103) between knowledge and preventive practices. This suggests that knowledge alone may not sufficiently influence behaviour, and that other factors such as risk perception and social norms may also play a critical role. Overall, the study indicates a generally high level of knowledge and good preventive practices among parents at HPUSM. Nonetheless, targeted health education initiatives remain necessary to address knowledge gaps and promote sustained hygiene practices to curb the transmission of HFMD